SLEEP DEPRIVATION AND CIRCADIAN RHYTHM DISTURBANCES IN NEURODEGENERATIVE DISEASES: MECHANISMS, CLINICAL CONSEQUENCES, AND PREVENTIVE STRATEGIES - Daria Godlewska; Katarzyna Kleszczewska; Agnieszka Pruska; Natalia Senatorska; Julia Rarok; Hanna Pietruszewska; Monika Banaszek; Agata Panfil; Julia Błocka; Agata Lurka (International Journal of Innovative Technologies in Social Science, 2025)
Sleep and circadian rhythms play crucial roles in maintaining neural homeostasis, synaptic plasticity, and metabolic clearance within the brain. Increasing evidence indicates that chronic sleep deprivation and circadian misalignment are not merely symptoms of neurodegeneration but active drivers of its onset and progression. This review synthesizes current findings linking disrupted sleep and circadian regulation to neurodegenerative diseases, with emphasis on molecular mechanisms, clinical implications, and therapeutic opportunities. Mechanistically, sleep loss impairs glymphatic and meningeal lymphatic clearance of neurotoxic proteins, compromises blood-brain barrier integrity, and promotes oxidative stress, neuroinflammation, mitochondrial dysfunction, and clock gene dysregulation. These interconnected processes accelerate the aggregation of amyloid-β, tau, α-synuclein, and TDP-43, thereby amplifying neuronal injury. Clinically, sleep and circadian disturbances predict cognitive decline, neuropsychiatric symptoms, biomarker progression, and earlier disease onset across Alzheimer’s disease, Parkinson’s disease, and related disorders. Preventive and therapeutic strategies, including cognitive-behavioural interventions, light therapy, melatonin supplementation, orexin antagonism, and structured circadian routines, show promising neuroprotective potential. Restoration of sleep architecture enhances glymphatic clearance, reduces neuroinflammation, and stabilizes cognitive function. Recognizing sleep as a modifiable determinant of neurodegeneration reframes it from a passive state into an active therapeutic target, underscoring its pivotal role in preserving brain integrity and delaying neurodegenerative trajectories.